2021
DOI: 10.3390/ijms22073801
|View full text |Cite
|
Sign up to set email alerts
|

Granulocytes and Cells of Granulocyte Origin—The Relevant Players in Colorectal Cancer

Abstract: Colorectal cancer (CRC) is one of the most common malignancy and cause of cancer death worldwide, and it still remains a therapeutic challenge for western medicine. There is strong evidence that, in addition to genetic predispositions, environmental factors have also a substantial impact in CRC development. The risk of CRC is attributed, among others to dietary habits, alcohol consumption, whereas physical activity, food containing dietary fiber, dairy products, and calcium supplements have a protective effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 114 publications
(77 reference statements)
1
5
0
Order By: Relevance
“…The TAP scoring method is inclusive of all types of IC; therefore, pathologists need not exhaust themselves under high magnification to confirm a cell type. Increasingly, research has shown that granulocytes are part of the adaptive tumor immune response [ 18 , 19 ]; we have also observed weak to moderate PD-L1 expression in neutrophils around TC (Supplementary Fig. 1 ).…”
Section: Discussionsupporting
confidence: 51%
“…The TAP scoring method is inclusive of all types of IC; therefore, pathologists need not exhaust themselves under high magnification to confirm a cell type. Increasingly, research has shown that granulocytes are part of the adaptive tumor immune response [ 18 , 19 ]; we have also observed weak to moderate PD-L1 expression in neutrophils around TC (Supplementary Fig. 1 ).…”
Section: Discussionsupporting
confidence: 51%
“…T cells work by helping to respond directly to infected body cells while B cells work to produce antibodies for infected body cells [12]. Granulocytes are components of white blood cells that have the ability to phagocytize and consist of neutrophils, basophils and eosinophils [13]. Red blood cells are an important component that contains about 95% of hemoglobin to circulate oxygen to each cell through the process of diffusion [14].…”
Section: Resultsmentioning
confidence: 99%
“…In our analysis of the total counts of eosinophils and basophils in the blood relative to CRC, we observed a negative association between these two factors. Regarding basophils, studies indicate that their high levels are associated with better overall survival and disease-free survival in patients with CRC, 25 suggesting they may suppress tumor progression by secreting histamine 26 and pro-inflammatory cytokines, such as TNFα, IL-6, and IL-1β, thereby enhancing the recruitment of specific CD8+ T cells and promoting cancer cell apoptosis. 27 Our findings imply that basophils may play a key role in regulating immune responses and suppressing CRC and that their levels are negatively correlated with the prognosis of patients with CRC.…”
Section: Discussionmentioning
confidence: 99%